Effect of some Essential Oils on Seed Germination and Seedling Length of Parthenium hysterophorous L. - Paudel, V. R.; Gupta, V.N. P. (Ecoprint: An International Journal of Ecology, 2009)
Effect of plant essential oils on seed germination and seedling growth of Parthenium hysterophorus was examined. Essential oils of Eucalyptus, Camphor, and Lemongrass were used in the experiments at different concentrations (0 to 20 ml.l-1). Water imbibed (36 h) seeds were germinated at 25°C ± 1 in petriplates containing 3 layers of filter papers soaked in distilled water and added with 1.5 ml of a given essential oil of particular concentration. Experiments were carried out taking three replicas. Observations were made at an interval of 24 h from the 4th day of incubation till 20th. All essential oils significantly (P < 0.05) reduced seed germination irrespective of their sources. Effects of plant sources were, however, not significant (P>0.05). Key words: Noxious weed, terpenes, sesquiterpenes, essential oil. doi: 10.3126/eco.v15i0.1945 ECOPRINT 15: 69-73, 2008